REVIEW LITERATURE: POLICY OF BACKING FOR TRADING ORNAMENT CORALS AND ANEMON BY THE MINISTRY OF MARINE AND FISHERIES AFFAIRS - Septa Riadi; Yudi Wahyudin; M. Nur Arkham (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2018)
The purpose of article writing is to conduct a policy review of the Ministry of Maritime Affairs and Fisheries regarding the prohibition of trade in ornamental materials for the sustainability of community welfare. The research method used is a literature study to understand the relevant problems. On Mid-August 2016, the Minister of Maritime Affairs and Fisheries made a policy to prohibit the sale and purchase of ornamental coral in any form. This policy was made due to the higher level of coral damage. The policy provides a negative impact on the sustainability of life and income of fishermen and entrepreneurs engaged in ornamental coral. The results of LIPI's research through the COREMAP-CTI program assess coral damage caused by climate change, besides fishing activities with environmentally friendly fishing gear such as bombs and poisons that cause coral damage. The conclusion of this article states that coral trade is not the main cause of damage to coral reefs in Indonesia, so the policies issued by the MMAF will have a negative impact on the social and economic conditions of the people who depend on the trade in ornamental corals. Keywords: ornamental coral, policy, trading